Albendazole and mebendazole in the treatment of ancylostomiasis in school children between the ages of 6-15 in Swat, Pakistan - Mudassar Iqbal; Wali Khan; Fiaz Khan; Israr Khan (Journal of the Pakistan Medical Association, 2021)
Published in August 2021